Export promotion as a key element of development strategy (1998)
Looks at which are the most appropriate kinds of export promotion instruments; the role of the state; the institutional characteristics that export promotion bodies shouild have; and, the availability of financing for export operations.
Keywords: EXPORT PROMOTION